ROS-mediated M1 polarization-necroptosis crosstalk involved in Di-(2-ethylhexyl) phthalate-induced chicken liver injury - Guangxing Li; Menglin Wu; Kaiting Chen; Yue Xu; Xiandan Zhang; Yang Chen; Hong Zhang; Ruili Zhang; Xiaodan Huang (Poultry Science)
The widespread use of plasticizers poses a serious threat to the environment and poultry health. Di-(2-ethylhexyl) phthalate (DEHP) is a commonly used plasticizer that can cause liver damage with prolonged exposure. Oxidative stress is closely associated with DEHP toxicity. Macrophage polarization plays an important role in many physiological and pathological processes and regulates disease development. This study aims to elucidate the mechanism of chronic DEHP exposure leading to chicken liver injury through oxidative stress-induced M1 polarization-necroptosis. In this study, the DEHP exposure model of chicken liver and the single and co-culture model of LMH and HD11 cells were established. With increasing dose and time, DEHP decreased body weight, increased liver coefficient, raised activities of liver function indicators and caused pathological liver damage in chickens. Further studies revealed the increase of reactive oxygen species (ROS) level and malonaldehyde (MDA) content, and the decrease of total antioxidant capacity (T-AOC) level, total superoxide dismutase (T-SOD) and glutathione peroxidase (GSH-Px) activities, which led to excessive oxidative stress in the liver. In addition, there was increased infiltration of liver macrophages (CD68), upregulation of M1 polarization indicators (CD86, iNOS, IL-1β, TNF-α) and downregulation of M2 polarization indicators (CD163, Arg-1, IL-10, TGF-β) and appearance of necroptosis (RIPK1, RIPK3, MLKL). The vitro experiments confirmed the addition of N-acetylcysteine (NAC) inhibited M1 polarization and necroptosis. Besides, M1 polarization of HD11 cells promoted necroptosis of LMH cells in the HD11-LMH co-culture system. In brief, ROS-mediated M1 polarization-necroptosis is involved in DEHP-induced liver injury. This study provides a reference for environmental toxicant exposure in livestock and poultry farming.